PANDANGAN HUKUM ISLAM DAN HUKUM ADAT TERHADAP TRADISI MAPPADENDANG PADA MASYARAKAT SUKU BUGIS - Jumria; Kiljamilawati; Jamil, Muh. Jamal (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2024)
This study examines the perspectives of Islamic law and customary law on the Mappadendang tradition in the Bugis community of Lasiwala Village, Pitu Riawa District, Sidrap Regency. The research focuses on community views of the tradition and an analysis of its implementation from an Islamic legal perspective. Field research was conducted using sharia and sociological approaches. Primary data were collected through interviews with key informants, while secondary data were obtained from literature and online sources. The findings indicate that most of the community perceives Mappadendang as a cultural obligation performed after the harvest, while a minority considers it unnecessary. From the perspective of Islamic law, the tradition is deemed permissible (mubah) as it aligns with sharia principles and falls under the category of urf. The tradition fosters social benefits, such as strengthening community bonds, without harming non-participants. This study recommends preserving the Mappadendang tradition, particularly by the younger generation, to ensure cultural continuity. Local governments are encouraged to support its preservation through educational programs and cultural promotion.